(3eWGdY GdCfhGQ HehdO GdfHi GdeNJGQs - (3YHO Gddg ShjOGf,J (B1234 (3g` s
(3ChdgG (B:s
(3GdMeO ddg CQSd eMeO Udi Gdgd Ydjg hSde QMeI ddYGdejf CeG HYO agPg QSGdI dWjaI ai PcQ ehdOg Udi Gddg Ydjg hSde s
(3BNQgG (B:s
(3hcGf Oafg Udi Gddg Ydjg hSde djdI GdCQHYGA ef hSW GddjdI hbjd ZjQ Pdc hYGTJ HYOg GHfJg aGWeI QVi Gddg YfgG SJI CTgQ aeG VMcJ (B" (3ai Jdc GdeOI hMb dgG Pdc dCf cd eUjHI Jghf YfO gPg GdeUjHg aEfG ddg hEfG Edjg QGLYhf hdG Mhd hdG bhg Edi Gddg GdYdi Gs
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B17s
(3GdfSNI HgG MhGTs
(3JUhas
(3HgG fXGe GdJYbjHI s
(3JHUQI GdYfhGf (B:s
(3TQM s
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdeLGejYs